Regulation of hydrogenase formation is temperature sensitive and plasmid coded in Alcaligenes eutrophus. - Friedrich, C G (1983)
Alcaligenes eutrophus grew well autotrophically with molecular hydrogen at 30 degrees C, but failed to grow at 37 degrees C (Hox Ts). At this temperature the strain grew well heterotrophically with a variety of organic compounds and with formate as an autotrophic substrate, restricting the thermolabile character to hydrogen metabolism. The soluble hydrogenase activity was stable at 37 degrees C. The catalytic properties of the wild-type enzyme were identical to those of a mutant able to grow lithoautotrophically at 37 degrees C (Hox Tr). Soluble hydrogenase was not rapidly degraded at elevated temperatures since the preformed enzyme remained stable for at least 5 h in resting cells or was diluted by growth, as shown in temperature shift experiments. Immunochemical studies revealed that the formation of the hydrogenase proteins was temperature sensitive. No cross-reactivity was detected above temperatures of 34 degrees C. The genetic information of Hox resides on a self-transmissible plasmid in A. eutrophus. Using Hox Tr mutants as donors of hydrogen-oxidizing ability resulted in Hox+ transconjugants which not only had recovered plasmid pHG1 and both hydrogenase activities but also were temperature resistant. This is evidence that the Hox Tr phenotype is coded by plasmid pHG1.